Pemanfaatan Aplikasi ClassDojo Pada Mata Pelajaran Pendidikan Agama Islam di MTs Nurul Afifah Aceh Tenggara - Hidayaturrahmi, Hidayaturrahmi; Hasbi, Syaukani (Universitas Labuhanbatu, 2023)
This research aims to describe: (1) The use of the Classdojo application in Islamic religious education subjects at MTs Nurul Afifah Southeast Aceh. (2) Obstacles that occur in using the Classdojo application in Islamic religious education subjects at MTs Nurul Afifah Southeast Aceh. (3) Solutions implemented to overcome obstacles in using the Classdojo application in Islamic religious education subjects at MTs Nurul Afifah Southeast Aceh. This research was conducted at MTs Nurul Afifah Southeast Aceh in September-August 2023. This type of research is qualitative research using a qualitative descriptive approach which describes the use of the Classdojo application in Islamic religious education subjects at MTs Nurul Afifah Southeast Aceh. Research data was obtained through interviews with Islamic religious education lesson teachers who were the main source in this research, then interviews with the class teacher and two student parents, observations in the form of participatory observation and documentation as supporting data for the research. The research results show that teachers have used Classdojo as an application or learning medium in Islamic religious subjects by utilizing various features available in the Classdojo application. Then, in using the Classdojo application in Islamic religious education subjects, several obstacles occurred, namely signal and memory interference. Full cellphone, supporting facilities for using the Classdojo application. This research describes the solutions taken to overcome the obstacles that have occurred in the use of the Classdojo application in Islamic religious education subjects.